Water entry of slender segmented projectile connected by spring. (1st December 2020) - Wu, Zhengyang; Zhang, Chengchun; Wang, Jing; Shen, Chun; Yang, Liang; Ren, Luquan
Abstract: An object that enters the water experiences a large impact acceleration at the initial stage of water entry, which can cause structural damage to objects that are dropped or launched into the water. To reduce the peak impact acceleration, a spring-connected segmented projectile with compressible nose was designed. Through inertial measurement unit and high-speed camera, the influence of the nose compressibility on the initial impact acceleration was qualitatively investigated. The experimental results demonstrate that the introduction of a spring between the nose and the main body of the projectile can significantly suppresses the peak acceleration during the early stage of impact (0–50 ms). Furthermore, the maximum impact acceleration experienced by the main body is only related to the maximum compression of the nose without considering the spring stiffness. In addition, using the spring exerts a slight effect on the non-dimensional pinch-off times of the cavity but increases the initial velocity required for the occurrence of cavity pinch-off events on the side of the main body. Highlights: We designed a segmented projectile for the aim to reduce the peak acceleration. The using of spring can significantly suppress the initial peak acceleration. The reason of impact peak acceleration decreases was revealed.